Fracture characteristics of dental Ag–Pd–Cu–Au type alloys with respect to microstructure. (4th August 2014) - Niinomi, M.; Fukui, H.; Takahashi, S.; Fukunaga, K.; Hasegawa, J.
Ag–Pd–Cu–Au type alloys are low cost dental alloys used widely for inlays, crowns, clasps, bars and bridges. The various kinds of fracture characteristics of Ag–Pd–Cu–Au type alloys should be evaluated with respect to microstructure to prevent the catastrophic failure of the dental products mentioned above. The fracture characteristics evaluation of Ag–Pd–Cu–Au type alloys with respect to microstructure has not been carried out very often. In particular, the number of reports on fracture characteristics evaluated based on the fracture mechanics with respect to microstructure is extremely small. The tensile fracture characteristics, fracture toughness based on the fracture mechanics, effects of alloying elements on fracture characteristics, and fatigue characteristics of dental Ag–Pd–Cu–Au type alloys are therefore described with respect to microstructure in this paper.